(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Pulp Stones (PS) are discrete calcified masses found in the dental pulp. The purposes of this study were to calculate the prevalence of pulp stones in Bangladeshi adult’s undergone endodontic treatment and to report any observed associations between occurrence of pulp stones and sex, tooth type, dental arch, side and dental status. From 131 Bangladeshi adult patients, comprising 58 males and 73 females aged between 12-60 years, 148 teeth were examined under 2x magnifications on periapical radiographs pre-operatively, carefully removed roof of the pulp chamber, examined with magnified intraoral camera, and tried for orifices patency with narrow instrument. Directly observed stones, or any obstruction to negotiation to canal orifice, color change & any tactile sense of having stone like material in the pulp chamber treated as positive sign. Loose stones are then removed with curve probe like instruments; tight stones are loosen using narrow long fissure bur peripheral to stones. Pulp stones thus collected were scored as found or not found, and associations with sex, tooth type, dental arch, side and dental status noted. Pulp stones were found in 31 (23.66 percent) of the subjects and 31 (20.95 per cent) of the teeth treated. Occurrences were rare in premolars and cuspid (Almost zero percent) but significantly higher in molars (24.80 percent). If third molars were left out of analysis, pulp stones were more common in first molars than in second molars and in maxillary first molars than in mandibular first molars. Unrestored and intact molars displayed higher prevalence of pulp stones than carious and or restored molars. This study result will provide the readers significant clues about the pulp stones during canal negotiation. Pulp stones may also provide useful forensic information when examining dental records to identify deceased persons. JCMCTA 2015 ; 26 (2) : 62 - 66